Failure of metals II: Fatigue. (1st April 2016) - Pineau, André; McDowell, David L.; Busso, Esteban P.; Antolovich, Stephen D.
Abstract: In this interpretive review, fatigue in metallic systems is considered primarily from the perspective of interactions between the microstructure, the deformation mode and the mechanical state at both low and high temperatures. In Part 1 the development and early propagation of cracks is considered in terms of the basic damage mechanisms and the relative size of the crack with respect to applicable microstructural feature(s). In this section, a multistage grain scale approach to microstructure-sensitive fatigue crack formation and growth is presented which uses Fatigue Indicator Parameters (FIPs) to correlate these processes. Various FIPs parameters are discussed in terms of their indication of the state of fatigue. The development and early crack propagation is considered in the context of microstructure and notches, and probabilistic aspects of the notch fatigue problem are discussed. These features are integrated into a systematic approach for the selection of fatigue resistant microstructures for given applications. In Part 2, attention is focused on Ni-base superalloys and the interaction between oxidation, creep and microstructure (including coatings) in the formation and propagation of cracks. This part of the overview addresses both experimental and modelling aspects. Methodologies based upon fundamental physical processes are presented for understanding and predicting the development and propagation of fatigue cracks, including effects of sequential oxide type formation and of creep on either restraining or accelerating damage by oxidation. The variable fatigue resistance of discs in jet engines is seen to depend upon the variability of microstructure and its influence on the severity of creep/oxidation interactions. All of these factors are considered in the practical case where both temperature and loading parameters vary simultaneously (thermomechanical fatigue). A physics-based life prediction model considering the interactions of deformation and environmental damage is reviewed in terms of its applicability to life prediction of components.